The effectiveness of high-dose intravenous vitamin C for patients with coronavirus disease 2019: A systematic review and meta-analysis - Sang Gyu Kwak; Yoo Jin Choo; Min Cheol Chang (Elsevier, 2022)
Objectives: Vitamin C has anti-inflammatory effects. This review aimed to investigate the therapeutic effect of high-dose intravenous vitamin C (HDIVC) in patients with coronavirus disease 2019 (COVID-19). Methods: The following key phrases were searched for article inclusion: "Vitamin C OR ascorbic acid" AND "COVID-19 OR coronavirus disease 2019 OR severe acute respiratory syndrome coronavirus 2 OR SARS-CoV-2". Articles that utilized HDIVC for the management of patients with COVID-19 were included, whereas review articles and case reports were excluded from this review. Moreover, we performed a meta-analysis to evaluate whether HDIVC can reduce the length of hospital stay and in-hospital mortality rate of patients with severe COVID-19. Results: In total, eight articles were included in this review, and five studies were included in the meta-analysis. The length of hospital stay was not significantly different between the HDIVC and control groups. Also, although our meta-analysis showed a tendency for HDIVC to reduce the in-hospital mortality rate in patients with severe COVID-19, the in-hospital mortality rate was not significantly different between patients treated with HDIVC and those who did not receive HDIVC. Conclusions: Evidence supporting the therapeutic use of HDICV in COVID-19 patients is lacking. Further studies are required for drawing a clear conclusion on this topic.